2006
DOI: 10.1111/j.1745-6584.2006.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Anomalous Decline in Radon Precursory to an Earthquake

Abstract: Mechanisms for interpreting anomalous decreases in radon in ground water prior to earthquakes are examined with the help of a case study to show that radon potentially is a sensitive tracer of strain changes in the crust preceding an earthquake. The 2003 Chengkung earthquake of magnitude (M) 6.8 on December 10, 2003, was the strongest earthquake near the Chengkung area in eastern Taiwan since 1951. The Antung radon-monitoring station was located 20 km from the epicenter. Approximately 65 d prior to the 2003 Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 23 publications
2
50
0
Order By: Relevance
“…For example, the distance from the epicenter to the radon monitoring station for the 2003 Mw 6.8 Chengkung earthquake was about 20 km; this distance is quite similar to the epicenterstation distance of 25 km for the 1978 (M) 7.0 Izu-Oshima-kinkai earthquake of Japan. The observed radon anomaly precursory to the 2003 Chengkung earthquake (Kuo et al 2006b) also behaved similarly to that observed precursory to the 1978 Izu-Oshima-kinkai earthquake (Wakita et al 1980). Eighty-six days before the 2003 Chengkung earthquake (Fig.…”
Section: Radon-monitoring Methodssupporting
confidence: 74%
“…For example, the distance from the epicenter to the radon monitoring station for the 2003 Mw 6.8 Chengkung earthquake was about 20 km; this distance is quite similar to the epicenterstation distance of 25 km for the 1978 (M) 7.0 Izu-Oshima-kinkai earthquake of Japan. The observed radon anomaly precursory to the 2003 Chengkung earthquake (Kuo et al 2006b) also behaved similarly to that observed precursory to the 1978 Izu-Oshima-kinkai earthquake (Wakita et al 1980). Eighty-six days before the 2003 Chengkung earthquake (Fig.…”
Section: Radon-monitoring Methodssupporting
confidence: 74%
“…The observed v-shaped pattern prior to the three main shocks clearly progresses in a sequence of three stages (Kuo et al 2006 (Kuo et al 2006(Kuo et al , 2010a. During Stage 1, the radon concentration in ground water was fairly stable; there was an accumulation of tectonic strain and a slow, steady increase of regional stress.…”
Section: Application Of Recurrent Radon Precursors For Forecasting Lomentioning
confidence: 92%
“…Radon partitioning into the gas phase can explain the anomalous decreases of radon precursory to the earthquakes (Kuo et al, 2006). To support the hypothesis of radon volatilization from ground water into the gas phase, radon-partitioning experiments were conducted to determine the variation of the radon concentration remaining in ground water with the gas saturation at formation temperature (60 ℃) using formation brine from the Antung hot spring.…”
Section: In-situ Radon Volatilization Mechanismmentioning
confidence: 99%
See 2 more Smart Citations